(untitled) (Journal of Parents and Teachers, 2025)
The article starts with a question about whether parents should wait for things to happen or take the initiative and control everything themselves. While there is no definitive answer, there is a continuous thought process regarding how to act in these situations. Additionally, it presents the idea that proverbs often fill meals with friends and generate some controversy among parents.